The Backward Design Learning Strategy Based on Literacy and Numeracy for Sociology Academic Ability Tests - Andhy Surya Hapsara; Lutfi Efendi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Education in Indonesia faces the crucial challenge of strengthening literacy and numeracy, especially in Sociology, a subject demanding data analysis and interpretation of social phenomena. This challenge is compounded by the need to prepare students for the Academic Ability Test (TKA), which emphasizes critical thinking and questions based on literacy-numeracy models.This best-practice research aims to implement the Backward design strategy integrated with literacy and numeracy to enhance the readiness of Grade XII students at SMAN 7 Yogyakarta for the Sociology TKA. The strategy was conducted through three stages: 1) Identify Desired Results (understanding TKA question formats); 2) Determine Acceptable Evidence (formative and summative assessments, including external Try Outs/TO); and 3) Design Learning Experiences (differentiated instruction and innovative activities like "Bowling Litnum" and independent TKA question creation). The method used was descriptive qualitative with a subject of 70 Grade XII students who chose Sociology as an elective. The results showed a significant improvement in the group of students predicted to be eligible for the National Achievement-Based Selection (SNBP), with the average score of summative assessments and TO TKA reaching 75–78 (meeting the success target of ≥75). However, the overall average score remained below the target due to motivational differences between eligible and non-eligible students.The conclusion indicates that Backward design is effective in improving learning outcomes for motivated groups and successfully integrates literacy-numeracy into Sociology learning, while also creating transferable evidence-based practice. The key success factors were the synchronization of TKA blueprints and external collaboration.